KNOWLEDGE MAPPING OF PHARMACOECONOMIC ON DIABETES MELLITUS RESEARCH BASED ON SCOPUS DATABASE: A BIBLIOMETRIC ANALYSIS - Zulpadly, M Fiqri; Sasongko, Heru; Ermawati, Dian Eka (Journal of Ayub Medical College Abbottabad, 2025)
Background: Every year there are more people diagnosed with diabetes mellitus (DM). There is no bibliometric report on this subject despite the publishing on the pharmacology of diabetes mellitus. In order to do this, this study will conduct a bibliometrical analysis of the literature on the pharmaco-economic analysis of diabetes therapy. Methods: To find a bibliographic database of primary research on the subject. The Scopus database was searched for articles containing the terms "pharmacoeconomic" OR "cost effectiveness analysis" OR "cost minimization analysis" OR "cost benefit analysis" OR "cost utility analysis" AND "diabetes mellitus" on May 5, 2023. There are 63 documents from the years 1978 to 2023 were chosen. VOSviewer 1.6.16 was used to assess the data. Results: The most significant nations, universities, sources, journals, and authors are, in order of influence: the United Kingdom, Beijing University, Diabetes Care Journal, PharmacoEconomics Journal, and Vijan (United States). A therapy model that is applied with high effectiveness but low cost can be determined by doing a pharmacoeconomic study of all aspects of diabetes mellitus management. Cost-effectiveness and cost-utility are the two most important and varied aspects of this subject. Conclusion: By utilising pharmacoeconomic analysis, our results improve research collaboration and pinpoint the knowledge gaps required for applications in the management of diabetes mellitus.